ANALISIS LEVEL LITERASI LABORATORIUM KIMIA DARI CALON GURU IPA TAHUN PERTAMA - Zuhaida, Anggun; Imaduddin, Muhamad (Universitas Negeri Semarang, 2019)
Laboratory literacy is part of scientific literacy, in chemistry learning it is not only learning that is based on understanding concepts, but also requires a laboratory skill to test the truth of theories and to know the benefits of chemical learning in daily life. This study is aimed at describing the level of literacy in prospective science teacher students in the first year. Literacy conditions are needed by the lecturer in designing laboratory activities at the Basic Chemistry Practicum course as part of the course that students must follow. This research is a descriptive study with 35 subjects of science teachers with heterogeneous backgrounds in one of the LPTK in Central Java. Literacy levels include an understanding of the functioning of the tool, the introduction of materials at the basic level, and also an understanding of the laboratory background. Data collection uses reflection sheets that require them to document, describe their functions, and describe laboratory materials and dimensions. The results show that the level of literacy is at a low level in 60% of students, moderate in 35% of students, and high level in 5% of students. Seeing these conditions, before conducting laboratory activities in the first year, matriculation needs to be done through virtual laboratory activities as well as demonstrations to be more effective.